Application of brain limbic system to adaptive cruise control. (1st January 2013) - Kim, Changwon; Langari, Reza
In this paper, we propose an application of neuromorphic based control strategy to achieve Adaptive Cruise Control (ACC) as an autonomous vehicle function. In this approach, a computational model of the brain limbic system is utilised to produce the required control action. The results demonstrate that the proposed controller has at least similar and generally better performance than the conventional approach. Finally, BLS based ACC approach is extended to platoons of vehicles. The results show the successful operation of the proposed approach in the platoon setting both in terms of individual vehicle performance as well as string stability of the platoon.